Kepemimpinan Visioner Sebagai Strategi Manajerial PAUD: Studi Literatur - Fitria, Diana; Nur Adzijah, Zahra; Fariha Ramadhani , Galuh; Miftah Agnia, Lanny; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze visionary leadership as a managerial strategy in Early Childhood Education (ECE) institutions. Early childhood is considered the golden age that determines holistic development, requiring institutions to have well-planned and sustainable management. The research employs a literature study method by reviewing books, journals, and academic articles related to visionary leadership and ECE management. The findings reveal that visionary leadership plays a strategic role in shaping the direction of institutions, not only functioning as administrative management but also as a guiding force that formulates long-term goals aligned with children’s developmental needs and societal demands. Visionary leaders establish clear visions and missions, which serve as guidelines for curriculum planning, program development, and resource management. The advantages of visionary leadership include inspiring teachers to be creative and innovative, fostering collaborative work culture, and creating a conducive learning environment. However, challenges remain, such as limited resources, resistance to change, and difficulties in consistently communicating the vision to all stakeholders. Theoretically, visionary leadership integrates elements of transformational, charismatic, and cultural leadership, emphasizing long-term vision, effective communication, and collective commitment. Thus, visionary leadership can be considered a relevant managerial strategy to improve the quality of ECE institutions, strengthen public trust, and ensure sustainability in the face of dynamic educational changes.